Novel patch biomaterial treatment for colon diverticulosis in swine model - Guo, Xiaomei; Patel, Bhavesh; Han, Ling; Van Alstine, William G.; Noblet, Jillian N.; Chambers, Sean D.; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2023)
Current leading managements for diverticular disease cannot prevent the recurrence of diverticulitis, bleeding and/or other complications. There is an immediate need for developing new minimal invasive therapeutic strategies to prevent and treat this disease. Through a biomechanical analysis of porcine colon with diverticular lesions, we proposed a novel adhesive patch concept aiming at mechanical reconstruction of the diseased colon wall. This study aims to evaluate the surgical feasibility (safety and efficacy) of pulmonary visceral pleura (PVP) patch therapy using a pig model of diverticulosis. Six female Yucatan miniature pigs underwent collagenase injection (CI) for the development of diverticular lesions. The lesions in each animal either received patch implantation (treated group, n = 40 for 6 pigs ) or left intact (untreated group, n = 44 for 6 pigs). The normal colonic wall in each animal received patch implantation at two spots to serve as control (n = 12 for 6 pigs). After 3 months of observation, the performance and safety of the patch treatment was evaluated through macroscopic and histological examination. We found that 95% of pouch-like herniation of the mucosa was prevented from the colon wall with the treatment. The pouch diameter was significantly reduced in the treated group as compared to the untreated group (P < 0.001). The patch application caused a significant increase in the levels of collagen of the colon tissue as compared to the untreated and control groups (P < 0.001). No difference was found in the lymphocyte and macrophage inflammatory infiltrate between the groups. Our results suggest that patch treatment efficiently inhibits the diverticular pouch deformation and promotes the healing of the colon wall with a normal inflammatory response, which may minimize the risk of diverticulosis reoccurrence and complications over time.